Seguimiento farmacoterapéutico en pacientes con enfermedad renal crónica atendidos en el Hospital General Machala. - Freire Farías, Ronny Alcívar; Andrade Mendoza, Genesis Samantha (My University, 2025)
Chronic kidney disease (CKD) represents a global public health challenge, with high prevalence and significant health costs, especially in patients with comorbidities such as hypertension and diabetes. The objective of this study was to apply a pharmacotherapeutic follow-up program in patients with CKD at the General Hospital of Machala, using the Dáder method to improve the quality of life of patients. This study was conducted at the Machala General Hospital of the Ecuadorian Institute of Social Security (IESS), applying a pharmacotherapeutic follow-up program in 41 patients with CKD. The design was non-experimental, observational and descriptive, developed between March and July 2025. The participants, over 18 years of age, were selected by non-probabilistic convenience sampling. Follow-up was performed using the Dáder method, which included interviews, evaluation of the pharmacological profile and telephone monitoring. The phases included sociodemographic data collection, analysis of prescribed medications, identification of medication-related problems (DRP), interactions, adverse effects and medication-associated negative outcomes (MAR). The information was processed with descriptive statistical tools, allowing the assessment of adherence to treatment, clinical effectiveness and therapeutic safety. The results showed that 82.93% of the patients had polypharmacy (average of 6.35 drugs), with a higher frequency in advanced stages of CKD. Moderate (71.25%) and severe (18.75%) drug interactions were common, with combinations such as aspirincarvedilol, amlodipine-simvastatin, losartan-aspirin, among others, standing out. Pharmacotherapeutic follow-up showed a reduction in DRP, such as adverse reactions (from 2 to 0 cases) and medication forgetfulness (from 24 to 13 cases). In addition, prevalent comorbidities were identified, such as arterial hypertension (33.61%) and diabetes (13.45%). This, the study showed the complexity of pharmacological management in CKD, highlighting the need for continuous follow-up to minimize risks and improve adherence, demonstrating that pharmaceutical intervention was key to optimizing treatment and reducing negative outcomes associated with medication.
La enfermedad renal crónica (ERC) representa un desafío global en salud pública, con alta prevalencia y costos sanitarios significativos, especialmente en pacientes con comorbilidades como hipertensión y diabetes. El objetivo este estudio fue aplicar un programa de seguimiento farmacoterapéutico en pacientes con enfermedad renal crónica del hospital General de Machala, utilizando el método Dáder para mejoramiento de la calidad de vida de los pacientes. Este estudio se realizó en el Hospital General Machala del Instituto Ecuatoriano de Seguridad Social (IESS), aplicando un programa de seguimiento farmacoterapéutico en 41 pacientes con ERC. El diseño fue no experimental, con enfoque tipo observacional y descriptivo, desarrollado entre marzo y julio de 2025. Los participantes, mayores de 18 años, fueron seleccionados por muestreo no probabilístico por conveniencia. El seguimiento se realizó utilizando el método Dáder que incluyó entrevistas, evaluación del perfil farmacológico y control telefónico. Las fases incluyeron recolección de datos sociodemográficos, análisis de medicamentos prescritos, identificación de problemas relacionados con medicamentos (PRM), interacciones, efectos adversos y resultados negativos asociados a la medicación (RNM). La información se procesó con herramientas estadísticas descriptivas, permitiendo valorar la adherencia al tratamiento, efectividad clínica y seguridad terapéutica. Los resultados demostraron que el 82,93% de los pacientes presentaban polifarmacia (promedio de 6,35 fármacos), con mayor frecuencia en estadíos avanzados de ERC. Las interacciones farmacológicas moderadas (71,25%) y graves (18,75%) fueron comunes, destacándose combinaciones como aspirina-carvedilol, amlodipinosimvastatina, losartán-aspirina, entre otras. Mediante el seguimiento farmacoterapéutico se observó una reducción de PRM, como reacciones adversas (de 2 a 0 casos) y olvidos en la medicación (de 24 a 13 casos). Además, se identificaron comorbilidades prevalentes, como hipertensión arterial (33,61%) y diabetes (13,45%). De este modo, el estudio evidenció la complejidad del manejo farmacológico en ERC, resaltando la necesidad de un seguimiento continuo para minimizar riesgos y mejorar la adherencia, demostrando que la intervención farmacéutica fue clave para optimizar tratamientos y reducir resultados negativos asociados a la medicación.
Keywords: ENFERMEDAD RENAL CRÓNICA; POLIFARMACIA; INTERACCIONES FARMACOLÓGICAS; REACCIONES ADVERSAS